Application of simplex centroid design in formulation and optimization of floating matrix tablets of metformin - Meenakshi Bhavesh Patel, Farhatjahan Shaikh, Vandana Patel, Naazneen Imtiaz Surti (Journal of Applied Pharmaceutical Science, 2017)
The purpose of this research work was to develop the buoyant matrices of metformin by the direct compression method using mixture design as an optimization technique. The simplex Centroid design was practiced as an optimization technique by modifying the quantity of three elements simultaneously and holding back their total concentration constant. Method: The amounts of HPMC K15M (X1), kappa-Carrageenan (X2) and sodium bicarbonate (X3) were used as the independent variables while floating lag time (Y1), % drug released after 1 hour(Y2) and time required for 90% (t90) were taken as the response variables. As per the simplex centroid design total 14 formulations were formulated. Matrices were evaluated for physical parameters, in-vitro buoyancy, swelling ability and adhesion retention period. Results: The results of response variables were statistically evaluated using design expert software. Formulation M-SCD 7 was found to be the optimum having good floating lag time and also matching the desirability criteria for drug release. The formulation also gave reasonably high adhesion retention period and swelling index desirable for securing the retention of formulation in the abdomen. Conclusion: It was concluded that the mixture of kappa carrageenan and HPMC K 15 M increases the flexibility in the release pattern of the drug. This study establishes the use of simplex centroid design in the development of floating matrix tablets with minimum experimentation.
Keywords: Simple centroid design, mixture design, metformin, gastro retentive, HPMC, carrageenan.